Dynamic relationships among non-oil revenue, government spending and economic growth in an oil producing country: Evidence from Nigeria - D. O. Olayungbo; O. F. Olayemi (Future Business Journal, 2018)
This paper investigated the dynamic relationships among non-oil revenue, government spending and economic growth in Nigeria for the period of 1981 to 2015. After establishing a long run relationship among the variables, the error correction model, impulse responses were estimated as well as the granger causality test among the variables. The results of the short run and long run showed negative effects of government spending on economic growth while non-oil revenue showed positive effect on economic growth. We also found non-oil revenue to have negative shocks on economic growth while the government spending shock was positive. The Granger causality revealed that government spending granger caused both non-oil revenue and economic growth supporting the Keynesian and spend-tax hypothesis in Nigeria over the period of the study. We recommend that the economy of Nigeria should be diversified into non-oil sector rather than relying solely on revenue from oil export.
Keywords: O23; O47; Q28; 650; Cointegration; Government spending; Impulse response; Nigeria; Non-oil revenue; Short run and long run